2020
DOI: 10.46456/jisdep.v1i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Rice Farmer Risk Management by Cropping Pattern Diversification in Rural West Java: Motivation, Behavior, and Perception

Abstract: The Indonesian government have implemented agricultural production cost insurance since 2015 called Asuransi Usaha Tani Padi (AUTP). It is an issue that the rate of farmer participation in the insurance is still low. As a challenge to increase participation, it becomes important to be aware of motivation, behavior, and perception that influence the practical risk management of farmers. This study investigated the relationship between cropping pattern diversification (as risk management) and factors such as mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Previously, Mutaqin and Usami [26] found that knowledge of insurance was one of the factors causing the low number of registrants for farming insurance. Additionally, based on the findings of research conducted by Fahad et al [13], the main factor that significantly influences farmers' decision to adopt agricultural insurance was extension services and increasing farmers' awareness about agricultural insurance products and procedures so that farmers can receive better benefits from insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Mutaqin and Usami [26] found that knowledge of insurance was one of the factors causing the low number of registrants for farming insurance. Additionally, based on the findings of research conducted by Fahad et al [13], the main factor that significantly influences farmers' decision to adopt agricultural insurance was extension services and increasing farmers' awareness about agricultural insurance products and procedures so that farmers can receive better benefits from insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Sementara Ramadani, Noor, and Yusuf (2021) juga menjelaskan petani di dalam menghadapi risiko produksi kecil. Dengan sikap menghadapi risiko netral (Mutaqin & Usami, 2020), risk averter (Bola & Prihtanti, 2019) dan (Defidelwina et al, 2019). Namun ada juga petani yang suka menghadapi risiko (Apriana et al, 2017).…”
Section: Pendahuluanunclassified
“…Oleh karenanya petani corporate di dalam antisipasi risiko gagal panen mengandalkan pengalaman panjang berusahatani dan lebih banyak melibatkan petugas penyuluh lapang. Hasil kajian Mutaqin and Usami (2020), petani sebelumnya menghadapi risiko tidak memiliki strategi penanggulangan kecuali mereka menyadari risiko yang dihadapi. Hal ini mengakibatkan penggunaan faktor produksi tidak terkendali.…”
Section: Risiko Produksiunclassified